Impact of hematite-silica composite nanofluids on interfacial tension and contact angle dynamics for electromagnetic-assisted enhanced oil recovery - Hassan, Yarima Mudassir; Guan, Beh Hoe; Chuan, Lee Kean; Nurul Hazlina, Noordin; Mohammed Falalu, Hamza; Sikiru, Surajudeen (Elsevier B.V., 2025)
The entrapment of a substantial volume of crude oil in subsurface reservoirs has caused extensive degradation of energy production globally. Various nanoparticles (NPs) were used in this regard; however, the performance of NPs was overwhelmed and consequently entrapped in the rock pores due to the unfavourable conditions of the reservoir. The electromagnetic (EM) driven approach was recently recognized as a suitable method for advancing nanofluid mobility in the geophysical porous media. Considering the combination of magnetic and dielectric attributes, forming smart composite nanofluids using hematite-silica (Fe2O3-SiO2) under EM waves will be consequential. The Fe2O3-SiO2 was synthesized using the sol-gel method. A visual test complemented by a zeta potential analyzer was used to determine the stability of the fluids. A goniometer was used for interfacial tension (IFT) and rock-oil wettability analysis, while a sandpack flooding method was used for the EOR experiment at 100C. The Fe2O3-SiO2 nanofluid stability achieved the highest electrostatic repulsion at −39 mV. When EM waves were propagated to the Fe2O3-SiO2 nanofluids, the IFT reduced from 17 ± 1.3 mN/m to 4.06 ± 0.6 mN/m. Similarly, the contact angle was reduced from 141 ± 3.5° to 71 ± 0.5°. The EM flooding experiment showed a total recovery of 56.68 to 79.94 % for Fe2O3-SiO2 in advance of the same composite nanofluids without EM wave endorsement (61.13 to 69.53 %). The EM wave propagation has energized the combination of permeability and permittivity in the Fe2O3-SiO2 nanofluids. Hence, an additional disturbance was generated at the oil-to-water interface, reducing IFT and contact angle, which enhanced fluids' transportation in a porous media and recovered additional oil. The environmental risks associated with Fe₂O₃-SiO₂ nanofluids discharge and mitigation strategies, such as magnetic recovery and biodegradable coating, have been evaluated. This work presents an innovative procedural development of EM-based techniques for subsurface fluid transport improvement to address environmental, engineering, and hydrological challenges in a geophysical porous media.